2022
DOI: 10.1155/2022/7283946
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Pembrolizumab Monotherapy for Recurrent/Unresectable/Metastatic Oral Squamous Cell Carcinoma: A Single-Center Study in China

Abstract: Background. Although pembrolizumab is recommended as a first-line treatment for advanced recurrent/unresectable/metastatic (R/U/M) head and neck squamous carcinoma, the differences in its efficacy among different populations need to be investigated. Methods. We reviewed 15 consecutive patients with R/U/M oral squamous cell carcinoma (OSCC) treated with pembrolizumab monotherapy at the Affiliated Hospital of Qingdao University between February 2021 and May 2022. All the 15 patients had known programmed death-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A total of 146 studies were ultimately included in our meta‐analysis 9,24–167 . A PRISMA diagram outlining our search is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 146 studies were ultimately included in our meta‐analysis 9,24–167 . A PRISMA diagram outlining our search is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Available evidence suggests that the use of PD-1 inhibitors is effective for certain tumor types. In recent years, the efficacy of the PD-(L)1 inhibitors (including camrelizumab, nivolumab, pembrolizumab and durvalumab) in OSCC has been reported in several studies (10)(11)(12)(13)(14). For instance, a previous study has shown that nearly 60% of patients with recurrent/unresectable/metastatic OSCC treated with pembrolizumab achieve objective response (10).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the efficacy of the PD-(L)1 inhibitors (including camrelizumab, nivolumab, pembrolizumab and durvalumab) in OSCC has been reported in several studies (10)(11)(12)(13)(14). For instance, a previous study has shown that nearly 60% of patients with recurrent/unresectable/metastatic OSCC treated with pembrolizumab achieve objective response (10). An additional study has revealed that the 1-year progression-free survival (PFS) rate is 25.4% in nivolumab-treated patients with R/M OSCC (11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations